Association of Glycemic Control with Platelet Indices Among Patients with Type 2 Diabetes Mellitus: Life Sciences-Biochemistry - Shanthi, B; Mohamed Rabeek, Jainulavudeen; Chandrika Anton, Mary; Kalai Selvi, V. S. (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus, a chronic metabolic disease affects various organs of the body on a long-term basis. Diabetes results in haematological changes that lead to development of complications such as hypercoagulability, anemia and cardiovascular disease (CVD). Hematological parameters play an important role in the treatment and follow up of diabetic patients. Hence, the objective of the study is to compare the mean levels of hematological parameters namely Platelet Distribution Width (PDW), Mean Platelet Volume (MPV) and Plateletcrit (PCT) between the type 2 diabetic patients with HbA1c ≥ 6.5 with the non-diabetic controls (HbA1c < 5.4) and to correlate the HbA1c values with the haematological parameters among type 2 diabetes patients. The case-control study was conducted for 6 months on 50 participants between the age group of 25-50 years. Case group includes 25 patients diagnosed with type 2 diabetic patients with HbA1c ≥ 6.5 and controls were healthy participants with HbA1c < 5.4. The serum samples were analysed for the haematological parameters namely PCT, PDW and MPV by electrical impendence method and HbA1c by immunoturbidimetric method. Increased levels of PCT, PDW, MPV were found among cases with HbA1c ≥ 6.5 when compared with the controls with HbA1c < 5.4. There was a significant association between platelet PCT, PDW and MPV with HbA1c among type 2 diabetes mellitus patients. Increased mean levels of platelet indices (PCT, PDW and MPV) were found to be significantly associated with glycemic control in type 2 diabetes mellitus. Hence, diabetic patients during their routine biochemical investigation, hematological investigation can also be done which helps in easy recognition of increased platelet indices that helps in treatment and prevention of disease progression among type 2 diabetes patients.